Abuya Saifuddin Amsir as The Rijal Dakwah - Adawiyah, Robiah; Uyuni, Badrah; Adnan, Mohammad (Bayyin: Jurnal Komunikasi dan Penyiaran Islam, 2023)
Saifuddin Amsir is one of the many betawi scholars who lived in the 21st century AD. he is known as a versatile preacher. he preached with various methods of da'wah. he preached with billisan, bilkitabah da'wah, bilhaal da'wah, and bittadhrib da'wah. This article uses a qualitative method with descriptive analysis. Saifuddin Amsir has nine abilities worthy of being a charismatic ulama star figure, including first, salafiyah, namely mastery of kitab kuning, second, kholafiyah, namely academics, third, hikmah, namely the ability to pray and wirid that has been routinized by experts, fourth, thoriqoh, namely dhikr to Allah SWT. fifth, tsaqowaf, namely cultural breadth, sixth, iqtishodiyah, namely economic capabilities such as being trusted to be a member of the DSN, seventh, tarbiyah, namely having an Education Foundation such as Ma'had Ali Zawiyah, eighth, harokah because he is an active person in mass organizations such as NU and finally ninth, siyasah, namely political ability.